Double liability in a branch banking system: Historical evidence from Canada - Anna Grodecka; Antonis Kotidis (Sveriges Riksbank, 2016)
We investigate the effects of the abolition of double liability requirement imposed on bank shareholders in Canada on bank risk-taking and lending behavior. Under the double liability rule, the shareholders of a bank were liable up to twice the amount of their subscribed shares in the case of bankruptcy. With the establishment of the Bank of Canada in 1934, the double liability requirement became less stringent and depended on the pace of the redemption of notes in circulation issued by the individual chartered commercial banks. Using historical balance sheet and accounting data, we show that the abolition of double liability was not accompanied by increased bank risk taking in Canada. Our findings are consistent with the literature that focuses on uniform regulations and nationwide branching as key financial stability elements in Canada.
Keywords: E44; G21; G28; N22; 330; Double Liability; Bank Risk-Taking; Leverage; Canadian banks; Financial Stability